The ermC leader peptide: amino acid alterations leading to differential efficiency of induction by macrolide-lincosamide-streptogramin B antibiotics. - Mayford, M (1990)
The inducibility of ermC by erythromycin, megalomicin, and celesticetin was tested with both wild-type ermC and several regulatory mutants altered in the 19-amino-acid-residue leader peptide, MGIFSIFVISTVHYQP NKK. In the model test system that was used, the ErmC methylase was translationally fused to beta-galactosidase. Mutational alterations that mapped in the interval encoding Phe-4 through Ile-9 of the leader peptide not only affected induction by individual antibiotics, but did so differentially. The subset of mutations that affected inducibility by the two macrolides erythromycin and megalomicin overlapped and were distinct from the subset of mutations that affected induction by celesticetin. These studies provide a model system for experimentally varying the relative efficiencies with which different antibiotics induce the expression of ermC. The possibility that antibiotics with inducing activity interact directly with the nascent leader peptide was tested by using a chemically synthesized decapeptide, MGIFSIFVIS--, attached at its C-terminus to a solid-phase support. This peptide, however, failed to bind erythromycin in vitro.